2016
DOI: 10.1007/s11695-016-2299-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Improvement of Hepatic Steatosis After Laparoscopic Roux-en-Y Gastric Bypass

Abstract: While weight loss and comorbidity improvement are common, they are not universal after LRYGB. Radiographic improvement of NAFLD in 84 % of patients was salutary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Weight loss has been associated with biochemical, 28 radiographic, 29,30 and histologic 31,32 improvements in NAFLD, but initial weight loss may be a challenge and maintaining lower weight after weight loss is difficult over time. 33 Weight loss and physical activity are the recommended treatments for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss has been associated with biochemical, 28 radiographic, 29,30 and histologic 31,32 improvements in NAFLD, but initial weight loss may be a challenge and maintaining lower weight after weight loss is difficult over time. 33 Weight loss and physical activity are the recommended treatments for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in hepatic left lobe volume on ultrasound was also observed after two years in 75 women who underwent laparoscopic AGB[98]. Two small studies found improvements in liver damage and NAFLD using ultrasound imaging[99] and CT[100].…”
Section: Hepatic Effects Of Bariatric Surgerymentioning
confidence: 99%
“…A recent meta-analysis indicated that 91% of patients undergoing RYGB experienced a reduction in the histological severity of liver steatosis after surgery [15]. Consistent with these observations, a study by Winder et al indicated a reduction in steatosis grade in 84% of patients after RYGB surgery [16]. When looking specifically at steatohepatitis, de Almeida et al reported a complete resolution of necroinflammatory changes and an improvement of liver fibrosis in all NASH patients undergoing RYGB [17].…”
Section: Discussionmentioning
confidence: 81%